Festividades, Culturas e Comunidades: Património e Sustentabilidade - Ribeiro, Rita; Araújo, Emília; Silva, Márcia; Fernandes, Alberto (2022)
Traditional and popular festivals are at the heart of communities' cultural and identity dynamics. Whether pilgrimages or carnival celebrations, dramatic enactments or religious rituals, festivals punctuate social and individual times and add meaning to collective life. Often considered at risk of fading or extinction due to changes in lifestyles and the massification and technologisation of cultures, festivities have been reinvigorated in recent decades. These processes of transformation and re-signification call for debate and reflection. With contributions from researchers from various continents, this work brings together 35 papers presented at the international conference "Festivals, Cultures and Communities: Heritage and Sustainability". It compiles a collection of ongoing research on festivals from a perspective that focuses on the relationship between festivities and communities, encompassing festive cultures and identities, the (re)valorisation of tradition and cultural and territorial sustainability. Moreover, considering contemporary trends, this publication focuses on the policies and processes of making festivals part of the heritage, their commodification and touristification, and the relationship between festivals, culture and power.